Criminal Liability for Child Grooming Operational Patterns in Mobile Legends Online Gaming - Fachri, Amanda Maharani; Harefa, Beniharmoni (Rechtsidee, 2025)
General Background—The rapid expansion of digital interactive spaces has intensified risks of non-physical sexual violence against children, particularly through online gaming platforms; Specific Background—Mobile Legends, one of Indonesia’s most popular multiplayer games, offers communication features that have been exploited by perpetrators to conduct child grooming through gradual trust-building and manipulation; Knowledge Gap—Indonesian criminal law does not explicitly regulate child grooming as a standalone offense, creating uncertainty in attributing criminal liability at pre-physical stages; Aims—This study analyzes the criminal liability of child grooming perpetrators operating through Mobile Legends within the framework of Indonesian law; Results—Using a normative juridical method, the study finds that perpetrators’ actions satisfy the elements of actus reus and mens rea under existing statutes, including child protection, electronic information, and sexual violence laws, even without physical contact; Novelty—The research integrates criminal liability theory with empirically identified grooming patterns in online gaming environments, emphasizing accountability at the preparatory and psychological manipulation stages; Implications—The findings suggest that while current laws can substantively address digital child grooming through systematic interpretation, effective enforcement requires enhanced digital forensic capacity, child-centered reporting mechanisms, and stronger collaboration with game platform providers to ensure comprehensive child protection in the digital era. Highlights: Digital Modus Operandi — Child grooming in Mobile Legends occurs through staged psychological manipulation using in-game and external communication features. Legal Accountability — Even without physical contact, grooming actions fulfill actus reus and mens rea under Indonesian child protection, ITE, and TPKS laws. Regulatory Urgency — The absence of explicit grooming provisions highlights the need for clearer norms and stronger digital law enforcement mechanisms. Keywords: Child Grooming, Online Gaming, Criminal Liability, Digital Sexual Violence, Indonesian Law